The application of a viability real-time PCR assay to detect viable Salmonella spp. in diarrheal stools: A spiked-stool study - Surangi H. Thilakarathna; Linda Chui (The Microbe)
Viability PCR (vPCR) is a development of real-time PCR where, a viability dye is used to irreversibly remove DNA from compromised or dead cells to selectively amplify live cell DNA. A vPCR assay using PMAxx™ as the viability dye was tested on Salmonella Enteritidis-spiked diarrheal stools to study the effects of stool concentration (5, 10 and 20 %) and PMAxx™ treatment conditions on the vPCR assay. Three replicates were used for each stool concentration, stool type and spiked cell concentration. A higher PMAxx™ concentration or an extended dark incubation time did not improve (heat-killed) HK-cell removal (Ct values for 100 μM/10 min vs 200 μM/30 min were 29.3 ± 1.6 vs 28.7 ± 0.9 for pooled liquid stool and 30.0 ± 1.3 vs 28.0 ± 1.4 for pooled semi solid stools respectively for 108 CFU/mL HK-cells). Spiked pooled liquid stool consisted of less stool matter and HK-cell DNA removal (Ct values ∼22, 28, 32 for 109, 108, and 107 CFU/mL) and live cell DNA detection (Ct values ∼16, 22, 30 for 108, 106, and 104 CFU/mL) was similar across the 3 stool concentrations. On the other hand, more stool matter in spiked pooled semi solid stool interfered with the vPCR assay and removed less HK-cell DNA (Ct values ∼27 vs 31 for 5 % vs 20 % stools with 108 CFU/mL) and detected less live cell DNA (Ct values ∼26 vs 21 for 5 % vs 20 % stools with 106 CFU/mL) at higher stool concentrations. Consequently, 5 % stool suspensions served best for spiked stool experiments overall to minimize false positive and false negative results. Although the Salmonella spp. positive stool (n = 20) concentration did not significantly affect the PCR or vPCR results overall, comparisons between stool concentrations of each stool showed better vPCR assay performance at low soft solid stool concentrations, i.e 5 %. Small sample size with focus on a single enteric pathogen and considering 2 types of stool consistencies are limitations of this study. This study explored the opportunity of using vPCR as a viability assessment tool when culture confirmation is unavailable in a clinical diagnostic world.